2016
DOI: 10.1039/c5cy01288k
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Cu-SSZ-13 by SO2 exposure under SCR conditions

Abstract: Sulfur poisoning is worse in SCR conditions as seen in the figure. Sulfur can be gradually removed during SCR conditions until a certain limit. Sulfur is removed more easily in the front part of the catalyst. Increased ammonia storage is observed due to storage on sulfur species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 53 publications
8
64
0
1
Order By: Relevance
“…Only a 12.6% reduction in the specific surface area was found for S-Cu-22. The sulfur species formation, caused by pore blocking, accounts for the reduction in the specific surface area, which agrees with many other studies [20,[28][29][30]. The result suggests that the CHA structure holds integrity during SO x sulfation.…”
Section: Bet and Xrd Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Only a 12.6% reduction in the specific surface area was found for S-Cu-22. The sulfur species formation, caused by pore blocking, accounts for the reduction in the specific surface area, which agrees with many other studies [20,[28][29][30]. The result suggests that the CHA structure holds integrity during SO x sulfation.…”
Section: Bet and Xrd Resultssupporting
confidence: 91%
“…Sandra et al [10] investigated the effect of sulfur-exposure temperature on the adsorption of sulfur over Cu/SSZ-13 and found that lower temperature lead to the adsorption of more sulfur, as well as lower SCR activity. Wijayanti et al [20,21] studied the effect of gas composition on SO 2 poisoning over Cu/SSZ-13 and found that the decrease in SCR activity is related to the formation of sulfate species and ammonium sulfate species. Luo et al [22] identified the response of two types of copper sites upon sulfur poisoning, and they found that Cu(OH) + , compared with Cu 2+ , easily combined with sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of SO2 at temperatures above 350 °C is clearly less, indicating that deactivation by SO2 is mainly relevant for the low-temperature performance, in agreement with earlier observations. [13][14][15][16][17][18][19][20][21][22][23][24] The low-temperature activity after SO2 exposure is partially restored by heating the Cu-CHA catalysts to 550 C in SO2-free gas ( Figure 1B). 13,14,17 The changes in the deactivation of NH3-SCR activity with time of SO2 exposure are illustrated in Figure 2A, which shows the deactivation, according to Eq.…”
Section: Nh3-scr Activity and Impact Of So2 Exposurementioning
confidence: 99%
“…Ultra-low sulfur diesel contains less than 10 wt ppm (Europe) or 15 wt ppm (US) sulfur, and the SO2 concentration in the exhaust gas typically reaches a few ppmv, which is nevertheless sufficient to reduce the low-temperature activity of the Cu-CHA catalysts significantly. [13][14][15][16][17][18][19][20][21][22][23][24] To be able to preserve the good lowtemperature activity, it is important to understand the impact of SO2 on the NH3-SCR activity of Cu-CHA based catalysts. We have recently shown that deactivation of Cu-CHA catalysts depends on the total SO2 exposure, which is the product of the SO2 concentration and the exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been carried out to learn about the reversible and irreversible damage of Cu-SSZ-13 such as dealumination of the framework structure, accumulation and distribution of different state copper species when Cu-SSZ-13 is subjected to sulfur poisoning [11][12][13]. These changes 2 of 16 are closely related with deactivation of the Cu-SSZ-13 catalyst.…”
Section: Introductionmentioning
confidence: 99%